Crystal structure of μ-terephthalatobis[bis(1,3-diaminopropane)- manganese(II)] diperchlorate, [Mn2{C3H6(NH2)2}4{C6H4(COO)2}][ClO4]2 - Xu S.-P. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
C20H44Cl2Mn2N8O12, monoclinic, P121/n1 (no. 14), a = 10.160(3) Å, b = 10.139(4) Å, c = 16.008(3) Å, β = 93.06(1)°, V = 1646.7 Å3, Z = 2, Rgt(F) = 0.069, wRref(F2) = 0.211, T = 293 K.